TINJAUAN TENTANG PENDISTRIBUSIAN PROGRAM BERAS MISKIN (RASKIN) DI KELURAAN SIDOMULYO TAHUN 2017 - Reny Afriani (ADMINISTRASI PUBLIK, 2018)
Reny Afriani, 2018, Overview of the distribution of program rice for the poor in the village of Sidomulyo, Faculty of Social and Politic Sciences, University of 17 August 1945, Mentor of Drs. H. Damai Darmadi,M.Si and Suhardiman,S.Sos,M.Si.This study aims to determine (1) The implementation of the distribution of the aid program, rice for the poor in the village of Sidomulyo (2) to determine the barriers that occur in the distribution process of implementation program of rice to poor to poor in the village of Sidomulyo.Methods this study is a qualitative research approach where the research conduvted is descriptive in the form of words written or spoken of the people or behaviors that are observed based on the theory that are relevant to the problems studied. Data analysis in this research uses four stages, namely the collection of information through interviews, data reduction, data presentation and conclusion.The results of this study indicate that (1) The Implementation of the distribution program rice for the poor in the village Sidomulyo Kecamatan Samarinda Ilir the city was effective because it was able to run well without any complaints from the citizens, only problems delay rice runs less effective in terms of the need for more coordination in depth with the head of bulog. (2) the bottleneck is the problem of delay in the arrival of rice to the village and efforts to deal with it is to continue to promote a positive attitude acting as the attitude of opennesss or honesty in distributing rice for the poor.